Soil-Supplied Silicon Alleviates Salinity Stress in Sunflower - Kabir, Md Enamul; Nahid, Naziur Rahman; Mahmud, Abdullah Al; Ali, Md Arman (Journal of the Bangladesh Agricultural University, 2025)
Silicon (Si), a beneficial metalloid, alleviates various abiotic stresses including salinity. Studies on Si-mediated alleviation of salinity stress of plants were mostly done in solution culture, very rare in soil culture including sunflower. Due to scarce literature on whether soil-supplied Si alleviates salinity stress in sunflower and there is no soil application rate of Si available for sunflower, the current pot study investigated for an optimum Si rate that can ameliorate the salinity effect. The 2-year (2022 and 2023) pot study consisted of two factors: (i) irrigation of crop 0 or 8 dS m-1 (ii) Si levels, 0, 0.1, 0.2, 0.3 g Si kg-1 soil with three replications. The results showed that salinity reduced the yield, yield attributes and dry matter significantly while application of Si gradually increased those yield parameters and seed yield. In case of sodium (Na), potassium (K) and Si uptake, salinity increased Na uptake and reduced K and Si uptake while application of Si decreased the Na uptake but increased the K and Si uptake. Silicon also increased the leaf number per plant and plant height. Among Si levels, 0.2 and 0.3 g kg-1 soil showed almost similar ameliorative effect of salinity. The results of the study suggest that soil application of Si can ameliorate salinity stress on sunflower and 0.2 to 0.3 g Si kg-1 soil should be suffice to ameliorate the negative effects of salinity. Studies on Si-mediated amelioration of salinity on sunflower and other suitable winter crops should be done in the farmers’ field of coastal region of Bangladesh where fresh water is scarce. J Bangladesh Agril Univ 23(1): 25–32, 2025